Preparation of Titanium Dioxide Nanoparticles Films by Air-Compressed Spray Method for Supercapacitor Device - Benchapol Tunhoo; Kanyawee Apiruktatarn; Korakot Onlaor; Thutiyaporn Thiwawong (IOP Conference Series Materials Science and Engineering, 2023)
Abstract In this work, the titanium dioxide (TiO 2 ) nanoparticle films were prepared from commercial Degussa P25-TiO 2 nanoparticles by air-compressed spray. The properties of the prepared films were characterized by X-ray diffraction, FTIR, Raman spectroscopy, and scanning electron microscope, respectively. In addition, the prepared TiO 2 film on a metal substrate (stainless steel, SS304) was used to fabricate the electrode of the electrochemical supercapacitor device. The electrochemical storage performance of the fabricated device was obtained by cyclic voltammetry measurement in aqueous 1 M Na 2 SO 4 with an Ag/AgCl reference electrode (platinum as a counter electrode). The optimum specific capacitance of the fabricated device was found at 3.014 F/g at a scan rate of 50 mV/s.
Keywords: Supercapacitor Materials and Fabrication; Catalytic Processes in Materials Science; Electrocatalysts for Energy Conversion